Water Quality and Loading of Pollutants from Shrimp Ponds during Harvesting - Ling, Teck Yee; Dunging, Buda; Nyanti, L.; Norhadi, I.; Emang, Justin J. (David Publishing, 2010)
Shrimp aquaculture is an important source of revenue for the state of Sarawak, Malaysia. However, th~~re were concerns on the impact of shrimp farming on the mangrove ecosystem due to the discharge of shrimp pond water to the surrounding environment and potential self-pollution through the intake ofsurrounding water for the shrimp ponds. Therefore, the objectives of this study were to determine the water quality ofthe harvesting pond water and quantify the pollutants loadings. Samplings were conducted in three ponds and three channels near the pond outflow in a commercial shrimp farm during complete draining of water at harvest. Results indicated that TSS and Chl-a were high in both the ponds and channels. Total ammonia-nitrogen was the predominant form of the inorganic nitrogen and the mean values in both the ponds and channels were more than 1 mglL which exceeded the maximum recommended for fish. Therefore, the water quality of the ponds and channel indicate that pond effluent should not be discharged directly into the surrounding environment but treated and nutrients recovered. Loads of total suspended solids, BODs, inorganic nitrogen, ammonia nitrogen, soluble reactive phosphorus and Chl-a of the effluent were quantified.